Analysis of Human Resources Competence for Improving Business Performance in The Masaran Sragen Batik Industry Centre - Pratiwi, Adcharina; Ricadonna, Nadia Adriane; Aditama, Rizky Ramadhan Aprian; Suranto, Suranto (Bulletin of Counseling and Psychotherapy, 2024)
The research aims to identify and analyse human resource competency variables in order to improve performance in Sragen Regency's batik industry centre. The research methods used were quantitative and qualitative data collection techniques through questionnaires, observation, interviews, and documentation. Employees from the Sragen batik industry centre participated in research activities. Data analysis procedures included validity testing, reliability tests, confirmatory factor analysis, and connection analysis of human resource competencies in order to improve Batik's business performance. According to the findings of the analysis, both intrinsic and extrinsic elements have an impact on increasing batik business performance.